Study of Control Coupling Effect and Differential Protection Adaptability of Offshore Wind Farm with MMC-HVDC Transmission System - HU Hong, XU Ling, ZHANG Mengyao, ZHANG Tian, LIN Yongchao, YAO Jun, HUANG Ruanming (Dianli jianshe, 2025)
High voltage direct current （HVDC） transmission technology based on modular multilevel converter （MMC） has become one of the mainstream solutions for large-scale offshore wind farms connected to the grid. When a short circuit fault occurs at the outgoing line of the sending system， the control coupling between the MMC station and the wind farm changes the fault current characteristics of the system significantly， which seriously affects the reliable of the relay protection device. In order to determine the influence of the control coupling effect of the MMC station and wind farm on the differential protection adaptability， the coupling mechanism of the system is analyzed based on the system control model， and the expression of the stable equilibrium point under the symmetric fault at sending end is derived. Secondly， the range of current reference and phase difference distribution under control coupling are defined. On this basis， the differential protection adaptability of the sending system is discussed， and the influence of system control coupling on protection reliability is summarized. Finally， the time-domain simulation model of the system is established， and the simulation results verify the correctness of the theoretical analysis.